(untitled) (KYAMC Journal, 2017)
Kikuchi’s disease, also known as histiocytic necrotizing lymphadenitis, is a rare entity with classic clinical findings of cervical lymphadenopathy and fever. Although Kikuchi’s disease does predominantly affect young women, it can appear at all ages; irrespective of gender. The rarity of the disease has led us to report this case. The clinical features and diagnosis have been discussed with review of literatures about this uncommon entity. Our patient, a young female of 20 years presented in a rural tertiary care hospital with features of upper respiratory tract infection and discrete lymphadenopathy on the left cervical region; fine-needle aspiration cytology revealed the diagnosis of Kikuchi’s disease. She received a course of antibiotics and showed complete recovery over a month. Last follow-up about 3 years later till writing this report she was found normal. The cause of Kikuchi’s disease is unknown, although infectious and autoimmune etiologies have been proposed. The disease usually runs a benign course with complete recovery. While rare, Kikuchi’s disease should remain in the differential diagnosis during evaluating a patient having lymphadenopathy. Its initial clinical appearance is commonly similar to that of a lymphoma, and it can be pathologically misdiagnosed as such. Despite the fact that Kikuchi’s disease is benign, an accurate diagnosis is important because misdiagnosis might lead to unnecessary surgery and/or chemotherapy. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 419-422